(3QSGdI aj GdMeO dIs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hgh MSHi hfYe Gdhcjd hHYO agPg ebOeI Ydi GdMeO dI afbhd GdMeO gh GdhUa HGdLejd Ydi GdLejd GdENJHGQi s
(3BNQgG (B:s
(3hai aYd GddSGf ai ebGWYI ZjQ GdfYeI MO dZhi hai aVd GdLfGf hGdCQcGf aYd ai ebGHdI hTcQ dZhi JeJ GdQSGdI HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B31s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG Jedc HGSe EHQGgje Hf eMeO GdMfai HJGQjN (B1071 (3g`s
(3hHBNQg fbhd ddeDda hgh YHGQI Yf UhQg eG cJHI GdeQMhe GdeDda ai Mb GdTjN eMi GdOjf Hf YQHis
(3HgGeTI JYdjbGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs